2010
DOI: 10.1097/rli.0b013e3181efd6b2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor 2-Specific Microbubbles for Molecular Ultrasound Detection of Prostate Cancer in a Rat Model

Abstract: The target-specific contrast agent was superior to the unspecific US contrast agent both with regard to early inflow analysis and specific accumulation in prostate cancer after 20 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
1
21
0
3
Order By: Relevance
“…Studies in mice and rats have shown promising results for different types of cancer. For prostate cancer, microbubbles targeting vascular endothelial growth factor receptor 2 (VEGFR2) have been successfully tested [52, 53]. Contrast may be further enhanced by using dual-targeted microbubbles, which have a higher binding efficiency, as shown by Willmann et al who targeted αvβ3 integrin as well as VEGFR2 [54].…”
Section: Molecular Imaging Applications In Cancer Diagnosis and Stmentioning
confidence: 99%
“…Studies in mice and rats have shown promising results for different types of cancer. For prostate cancer, microbubbles targeting vascular endothelial growth factor receptor 2 (VEGFR2) have been successfully tested [52, 53]. Contrast may be further enhanced by using dual-targeted microbubbles, which have a higher binding efficiency, as shown by Willmann et al who targeted αvβ3 integrin as well as VEGFR2 [54].…”
Section: Molecular Imaging Applications In Cancer Diagnosis and Stmentioning
confidence: 99%
“…In addition, with the assistance of ARF, recent studies have also demonstrated ultrasound targeted molecular imaging in large vessel environments using some new techniques(Mauldin et al, 2012; Patil et al, 2011; Wang et al, 2013b). In summary, state-of-the-art ultrasound molecular imaging methods have demonstrated efficacy in pre-clinical studies for detection and monitoring of various types of cancers (Bzyl et al, 2011; Fischer et al, 2010; Pysz et al, 2010)as well as cardiovascular inflammation (Kaufmann et al, 2007; Masseau et al, 2012). However, these approaches possess some limitations such as requiring a “control injection” (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Zr-89 bevacizumab imaging has been used in the monitoring of tumor angiogenesis. Ultrasound has been used to image VEGF distributions in vivo [60]. Microbubbles can be covalently coupled to VEGF constructs have been used for intravascular imaging [61].…”
Section: Other Molecular Imaging Techniques For Plaque Angiogenesismentioning
confidence: 99%